Aid and growth: new evidence using an excludable instrument - Dreher, Axel; Langlotz, Sarah (Discussion paper series, 2017)
We use an excludable instrument to test the effect of bilateral foreign aid on economic growth in a sample of 96 recipient countries over the 1974-2009 period. We interact donor government fractionalization with a recipient country’s probability of receiving aid. The results show that fractionalization increases donors’ aid budgets, representing the over-time variation of our instrument, while the probability of receiving aid introduces variation across recipient countries. Controlling for country- and period-specific effects that capture the levels of the interacted variables, the interaction provides a powerful and excludable instrument. Making use of the instrument, our results show no significant effect of aid on growth in the overall sample. We also investigate the effect of aid on consumption, savings, and investments, and split the sample according to the quality of economic policy, democracy, and the Cold War period. With the exception of the post-Cold War period (where abundant aid reduces growth), we find no significant effect of aid on growth in any of these sub-samples. None of the other outcomes are affected by aid.